1997
DOI: 10.1042/bj3240421
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an exogenous isopentenyl diphosphate isomerase gene enhances isoprenoid biosynthesis in Escherichia coli

Abstract: Escherichia coli expressing the Erwinia carotenoid biosynthesis genes, crtE, crtB, crtI and crtY, form yellow-coloured colonies due to the presence of beta-carotene. This host was used as a visible marker for evaluating regulatory systems operating in isoprenoid biosynthesis of E. coli. cDNAs enhancing carotenoid levels were isolated from the yeast Phaffia rhodozyma and the green alga Haematococcus pluvialis. Nucleotide sequence analysis indicated that they coded for proteins similar to isopentenyl diphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
3
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(121 citation statements)
references
References 32 publications
5
110
3
2
Order By: Relevance
“…both IPP and DMAPP (Eisenreich et al, 2004), previous work has suggested that IDI activity in the plastid is necessary for maximal rates of synthesis of isoprenoids such as carotenoids (Albrecht and Sandmann, 1994;Page et al, 2004). Furthermore, it has also been shown that in E. coli cells that were engineered to synthesize carotenoids from DMAPP and IPP produced via the MEP pathway, IDI activity was a limiting factor in carotenoid biosynthesis (Kajiwara et al, 1997;Cunningham and Gantt, 2000). That exogenously supplied mevalonate can complement a block in 1-deoxyxylulose 5-phosphate synthase activity and chlorophyll biosynthesis (presumably following the transport of IPP to the plastid) also suggests the presence of IDI activity in this compartment (Esté vez et al, 2000;Nagata et al, 2002).…”
Section: Shortened Transcripts Of Both Idi1 and Idi2 Are Expressed Thmentioning
confidence: 99%
“…both IPP and DMAPP (Eisenreich et al, 2004), previous work has suggested that IDI activity in the plastid is necessary for maximal rates of synthesis of isoprenoids such as carotenoids (Albrecht and Sandmann, 1994;Page et al, 2004). Furthermore, it has also been shown that in E. coli cells that were engineered to synthesize carotenoids from DMAPP and IPP produced via the MEP pathway, IDI activity was a limiting factor in carotenoid biosynthesis (Kajiwara et al, 1997;Cunningham and Gantt, 2000). That exogenously supplied mevalonate can complement a block in 1-deoxyxylulose 5-phosphate synthase activity and chlorophyll biosynthesis (presumably following the transport of IPP to the plastid) also suggests the presence of IDI activity in this compartment (Esté vez et al, 2000;Nagata et al, 2002).…”
Section: Shortened Transcripts Of Both Idi1 and Idi2 Are Expressed Thmentioning
confidence: 99%
“…We previously had taken advantage of this phenotype in the identification and functional analysis of a ␤-carotene hydroxylase from Arabidopsis (11). Also, a similar construct made with the gene equivalent to ipiHp2, and an isomerase gene from the yeast Phaffia rhodozyma, led to enhanced carotenoid accumulation in E. coli (32). In the mutant Car-3, which accumulates carotenoids at an earlier stage than wild type, a higher IPP isomerase content might be expected.…”
mentioning
confidence: 99%
“…One gene in the PR photosystem cluster was dispensable under our conditions: the idi gene that encodes IPP ␦-isomerase, an activity already present in E. coli (17), as is the FPP synthase, catalyzing the next two steps in the pathway (23). The presence of the idi gene in the cluster likely enables retinal production in the native organism because isomerization of IPP to dimethylallyl pyrophosphate can be a rate-limiting step in ␤-carotene biosynthesis (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…As expected for the regular isoprenoid side-chain, C 22 was the least abundant homologue. C 24 tetracyclic terpane was also detected in many samples. As the biological source(s) of cheilanthanes and C 24 tetracyclic terpane are not known , little paleobiological interpretation can be made of their presence.…”
Section: Cheilanthanes and Other Terpanesmentioning
confidence: 99%